PHYSICO-CHEMICAL CHARACTERIZATION OF SIDDHA SASTRIC FORMULATION ARUMUGA CHENDHURAM - Ramamurthy, *Murugan; Thanigavelan, Vembu; Manickavasakam, Kumarswamy (International Journal of Ayurveda and Pharma Research, 2016)
Arumuga Chendhuram is a herbo-mineral formulation cited in Siddha Vaidya Thirattu prepared through the special oxidation procedure involving purified form of minerals processed under herbal juice. It has been practiced frequently for treating inflammation of joints and anorectal disorders at 65-130 mg with the adjuvant Honey. The present study dealt with analyzing the physico-chemical characterization of Arumuga Chendhuram to establish standard quality parameters. Two samples of Arumuga Chendhuram (Self prepared and Pharmacy Samples) were subjected to analytical tests and quantitative analyzes using Sophisticated Instruments. Analytical analysis showed low level of moisture content and extractive values in both samples but ash values were high. The functional groups analyzed by FT-Raman Spectroscopic study inferred different numbers of peaks among the samples. The particles of both samples were in 1-10 micron size scanned under Electron microscope. Elements found in both samples were in its oxide form at different concentrations which was analyzed through Wavelength dispersive X-Ray Fluorescence. Both samples contain high concentration of ferric oxide. The concentration of trace and heavy metals were analyzed using Inductively Coupled Plasma - Optical Emission Spectrometer showed the presence of low concentration of Mercury, Arsenic and Iron in self prepared Arumuga Chendhuram. From the result of above studies, we inferred that Arumuga Chendhuram prepared by us was superior to Pharmacy product in quality and that physicochemical fingerprint shall be used as standard.